The Development of Innovative Colloidal Chemistry Teaching Module for XI Class of Senior High School Based on Project Based Learning - Leny Novita; Eddiyanto Eddiyanto; Manihar Situmorang (Jurnal Pendidikan Kimia (JPKim), 2016)
Abstract. The development paradigm of the potential of human resources resulted in demands in all areas, not just the quality of human resources, but human character itself. Learning innovations incorporated into textbooks is expected to improve the quality of education and develop the character of the nation's generation. This research aims to develop an innovative high school chemistry textbook/MA XI for second half class based on the 2013 curriculum standards that are used to create a creative learning, effective, and fun, and help learners gain optimal learning results. The population is all high schools in North Sumatra. The sample in this study were taken by purposive sampling, namely SMA Hang Tuah Belawan, SMAN 9 Medan and SMAN 19 Medan each as much as 2 classes. Experiment and Control Class. Data were analyzed by using independent sample t-test with SPSS 20 for windows at significance levela=0.05. Results showed that innovative chemistry textbook has been successfully developed into a complete teaching materials and interactive learning relevant to the subject matter on the chemistry and sub subject in the innovative textbook of the development results. Innovative textbook can be used to study the original teacher centered learning was transformed into a student centered learning.Keywords: textbook of chemistry, curriculum 2013, the PjBL model, high school